2019
DOI: 10.1016/j.compgeo.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

A method for calibration of the Hyperplastic Accelerated Ratcheting Model (HARM)

Abstract: This paper presents an analytical methodology for calibration of the Hyperplastic Accelerated Ratcheting Model (HARM) [3], based on a closed-form expression for the accumulation of ratcheting strain with cyclic history. The proposed method requires the fit of one test response and of a few continuous cyclic tests. The initial motivation for this work is the calibration of models for the design of piles subjected to longterm cyclic lateral loading, and the test results from Abadie, Byrne [1], [2] are used for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The calibration method is outlined in Abadie et al (2019), based on the experimental results of Abadie et al (2017), with the key steps of the method summarized in Appendix B.…”
Section: Key Modelling Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The calibration method is outlined in Abadie et al (2019), based on the experimental results of Abadie et al (2017), with the key steps of the method summarized in Appendix B.…”
Section: Key Modelling Featuresmentioning
confidence: 99%
“…The properties of the test piles are given in Table 2, while the load sequences for CM6 and CM5 are shown in Table 3 and Table 4 respectively CM6 involves a short series of cycles of three load-sets at increasing load magnitudes, while CM5 involves a more extensive series of load-sets, of larger numbers of cycles. Calibration follows the steps outlined by Abadie et al (2019), in which the model is expressed in terms of a normalized "stress" and normalized "strain". For the 0-D model:…”
Section: Field Test Datamentioning
confidence: 99%
See 1 more Smart Citation
“…-methods based on '0D' modelling of monopile-soil interaction. In this approach, distributed/continuum geotechnical mechanisms are lumped into a single macro-element formulated in terms of only a few pairs Abadie et al, 2019b). Non-linear monopile macro-elements have also been used to account for soilfoundation interaction effects in the dynamic analysis of OWTs (Page et al, 2019), and may potentially be extended to tackle cyclic loading conditions (di Prisco & Pisanò, 2011);…”
Section: Introductionmentioning
confidence: 99%
“…Cycleby-cycle assessment of monopile behaviour requires more advanced analysis, with constitutive models capable of capturing the governing mechanisms. Houlsby et al [29] introduced a hyperplasticity model for the general ratcheting response of a structure under cyclic loads, describing the continuous accumulation of permanent deformations with number of cycles, and this was calibrated by Abadie et al [2] for monopiles in dry sand. In saturated sands, coupled hydro-mechanical finite element (FE) analyses incorporating multi-surface plasticity models have shown that monopiles under cyclic loading can generate a partially drained response in the soil, with monopile performance influenced by transient pore pressure generation and dilative and contractive (liquefying) responses [4,11].…”
Section: Introductionmentioning
confidence: 99%